The effects of maternal brucellosis on pregnancy outcome - Maged Elshamy; Amien I. Ahmed (Journal of Infection in Developing Countries)
Background: Our aim was to assess the outcome of pregnancies complicated by Brucella infection. Design: Prospective study. Setting: EL-Hasan National Hospital, El-Rawad Clinic, TAIF, SAUDI ARABIA (where the practical part of the study was accomplished) and Obstetrics and Gynecology Department, Mansoura University Hospital (where the theoretical part of the study was completed). Methods: This study was conducted from August 2005 to December 2007. Tube method for detection of antibody titre for brucellosis was performed on 450 pregnant women; 415 had no symptoms or signs of brucellosis and 35 had symptoms and signs of the disease.The antibody titre was positive in 55 pregnant women (group 1) and negative in 395 pregnant women (group 2). Both groups were followed up during pregnancy and the neonatal period to determine any type of reproductive failure. Results: The incidence of brucellosis was 12 .2 % among pregnant women included in the study. The incidence of abortion in group I was 27.27%; IUFD was 12. 72%; and preterm labour was 10.90%. There were statistically significant differences in the abortion and IUFD rates but no significant difference in the preterm labour rates between the test and control groups. There was a statistically significant difference in abortion rates between patients with a titre more than 1/160 and those with a titre less than 1/160 (p=0.03). Conclusion: The frequency of fetal loss among patients with brucellosis is very high. It is advisable to have a high degree of alertness for brucellosis in endemic areas.